Case Report : Karsinoma Duktal Invasif pada Payudara Pria - Danisa Indira Fatma; Muharriansyah Muharriansyah (Pusat Riset dan Inovasi Nasional, 2025)
Breast cancer is a rare disease in men, accounting for approximately 0.5-1% of all breast cancer cases. Although current data show a slow increase in incidence, epidemiological data on male breast cancer are still limited compared with female breast cancer due to its rarity. This case study discusses a 70 year old man with a previous history of invasive ductal carcinoma who presented with complaints of a hard lump in the right breast that had recurred several times. Biopsy results showed invasive ductal carcinoma. The patient had previously undergone a radical mastectomy of the right breast, but the patient refused adjuvant chemotherapy after the initial dissection. Based on the tumor stage, it was found to be T4bN1M0 and then a mastectomy was performed. Based on this case, it was found that the importance of complete and comprehensive treatment of invasive ductal carcinoma in men is expected to become a guide to promote additional treatment for removal of the primary tumor in male breast cancer.